Postactivation performance enhancement (PAPE) of sprint acceleration performance. Issue 9 (2nd September 2022) - Brink, Nicholas J.; Constantinou, Demitri; Torres, Georgia
ABSTRACT: Postactivation performance enhancement (PAPE) is a principle that an acute bout of high-intensity voluntary exercise is followed by an enhancement in strength, speed or power production. This study intended to show a direct correlation between intensity, specificity and the outcome of a maximal task of sprint accelerations compared to a previously defined weighted plyometric intervention. In a randomised controlled, double-blind trial, professional footballers undertook 20 m maximal sprint accelerations at a baseline and at 2 and 6 min post-intervention after 1 of 3 interventions; 2 repetitions of 20 m sprint accelerations (S), 3 × 10 alternative leg weighted bounding (P) and control (C). Relative to the baseline there was a significant improvement for S over 10 and 20 m at 2 min of 0.12m.s −1 and 0.11m.s −1 and 6 min of 0.11m.s −1 and 0.12m.s −1 . Relative to the baseline P also had a significant improvement over 10 and 20 m at 2 min 0.09m.s −1 and 0.09m.s −1 and 6 min of 0.11m.s −1 and 0.09m.s −1 . There was a significant improvement in C between 2 and 6 min post-intervention at 10 and 20 m of 0.06m.s −1 and 0.08m.s −1 . This finding suggests a maximal sprint acceleration may enhance the outcome of a subsequent maximal sprint acceleration at 2 min, but the latter results could not be directly attributed to the interventions as previous testing is likely to have influenced these outcomes.